Impact of time to return of spontaneous circulation on neuroprotective effect of targeted temperature management at 33 or 36 degrees in comatose survivors of out-of hospital cardiac arrest. (November 2015) - Kjaergaard, Jesper; Nielsen, Niklas; Winther-Jensen, Matilde; Wanscher, Michael; Pellis, Tommaso; Kuiper, Michael; Hartvig Thomsen, Jakob; Wetterslev, Jørn; Cronberg, Tobias; Bro-Jeppesen, John; Erlinge, David; Friberg, Hans; et al.
Abstract: Aim: Time to Return of Spontaneous Circulation (ROSC) has a plausible relation to severity of hypoxic injury before and during resuscitation in Out-of-Hospital Cardiac Arrest (OHCA), and has consistently been associated with adverse outcome. The effect of Targeted Temperature Management (TTM) may not be similar over the full spectrum of time to ROSC. This study investigated the possible beneficial effect of targeting 33 °C over 36 °C on the prognostic importance of time to ROSC. Methods: In predefined sub-study of the TTM-trial (NEJM 2013) we investigated the relationship between time to ROSC, level of TTM and mortality and neurological outcome as assessed by the Cerebral Performance Category (CPC) scale and modified Rankin Scale (mRS) after 180 days. Results: Prolonged time to ROSC was significantly associated with increased mortality with a hazard ratio (HR) of 1.02 per minute (95% CI 1.01–1.02). Level of TTM did not modify the association of time to ROSC and mortality, p interaction  = 0.85. Prolonged time to ROSC was associated with reduced odds of surviving with a favorable neurological outcome for CPC ( p  = 0.008 for CPC 1–2) and mRS ( p  = 0.17, mRS 0–3) with no significant interaction with level of TTM. Conclusion: Time to ROSC remains a significant prognostic factor in comatose OHCA patients with regards to risk of death and risk of adverse neurological outcome. For any time to ROSC, targeting 33 °C in TTM was not associated with benefit with regards to reducing mortality or risk of adverse neurological outcome compared to targeting 36 °C.